2020
DOI: 10.1021/acs.cgd.0c00088
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Structure and Flexibility of Coordination Polymers via Solvent Control of Tritopic Triazine Conformation during Crystallization

Abstract: Soft crystallization routes for the controlled growth of one- and two-dimensional Cu­(II)-coordination polymers of the type [(Cu­(hfa)2) x (3-tpt)] n (hfa = hexafluoroacetylacetonate, 3-tpt = 2,4,6-tris­(3-pyridyl)-1,3,5-triazine) are described. Three volatile solvents with different protic/aprotic characteristics were chosen as the reaction media, e.g., supercritical CO2, chloroform, and ethanol. Five (1–5) new compounds were crystallized, with different structures and Cu­(II)/3-tpt ratios. The structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…On the other hand, d1Dplot is being continuously used in studies that involve crystallographic changes of the sample in situ, e.g. to follow crystallographic changes during chemical reactions, temperature ramps or gas absorption of porous materials [32].…”
Section: Applicationsmentioning
confidence: 99%
“…On the other hand, d1Dplot is being continuously used in studies that involve crystallographic changes of the sample in situ, e.g. to follow crystallographic changes during chemical reactions, temperature ramps or gas absorption of porous materials [32].…”
Section: Applicationsmentioning
confidence: 99%
“…A variety of studies have demonstrated the coordination nanostructures by altering organic ligands, such as carboxylate, 3,5,12,18 hydroxyl, 14,20,21 pyridine, 9,22-25 and triazine. [26][27][28][29][30] The triazine derivatives are important in a range of areas as ligands for supramolecular self-assembly of more complex mixed layers, hence it may be interesting to study the coordination properties of the triazine derivatives. In this article, we fabricated different coordination nanostructures by 4,4 0 ,4 00 -(1,3,5-triazine-2,4,6-triyl) tribenzoic acid (TATB) molecules coordinating with Cu 2+ or Fe 3+ ion with different concentrations on highly oriented pyrolytic graphite (HOPG) surface.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 Recently, three polymers of the type [(Cu(hfa) 2 )(3-tpt)] n [hfa = hexafluoroacetylacetonate, 3-tpt = 2,4,6-tris(3-pyridyl)-1,3,5-triazine] have been described, whose composition only differs in the incorporated crystallization solvent molecules but forms structures differing in dimensionality and porosity. 12 Actually, a survey of the scientific literature regarding MOF supramolecular isomerism indicates that many authors do not take into consideration differences in the content of crystallization solvents, 11 although the strict criterion to name isomerism would require exactly the same composition. 40 Overall, the crystal structures of 2−4 represent a major example of packing isomerism and offer interesting clues to understand how a packing mode over the others can be favored as a function of the crystallization solvent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The tendency of some MOFs to polymorphism has been related to the low energy differences between the lattice energy for diverse polymorphs of only a few kcal mol –1 . Experimental factors, such as the temperature, reagent concentration, pH, solvent, presence of additional species in the medium (additives, template/guests), crystallization method, and so forth, would determine the particular isomer obtained in a designed synthetic process. , Among all these factors, the use of different solvents to precipitate different supramolecular isomers is relatively common. Different solvent properties may favor the formation of distinct isomers: polarity, ability of solvent molecules to coordinate with the metal ion, binding to the crystal nucleus, formation of loose aggregates of several solvent molecules that can serve as effective templates, and so forth. Thus, varying the energy barrier leads to different polymorphs. , …”
Section: Introductionmentioning
confidence: 99%